2021
DOI: 10.3390/insects12121075
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Entomology: How Is Gibson’s Framework Useful?

Abstract: To date, numerous studies have demonstrated the fundamental role played by optic flow in the control of goal-directed displacement tasks in insects. Optic flow was first introduced by Gibson as part of their ecological approach to perception and action. While this theoretical approach (as a whole) has been demonstrated to be particularly suitable for the study of goal-directed displacements in humans, its usefulness in carrying out entomological field studies remains to be established. In this review we would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…The relative rate of expansion r or the optical variable τ are both measures of the remaining time before collision (time-to-contact) without requiring any explicit measurement of the relative distance of the animal from the object or the speed of the animal ( Lee, 1976 ; Gibson, 1986 ). From a pure viewpoint of the Gibson’s framework, these perceptual variables can be measured directly by an animal’s visual system (including human's) to estimate the time-to-contact ( Gibson, 1986 ; Serres and Ruffier, 2017 ; Dauxère et al., 2021 ). The relative rate of expansion r or the optical variable τ encodes the ratio of approach velocity V and distance to the landing surface y as r = V / y or τ = y / V ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…The relative rate of expansion r or the optical variable τ are both measures of the remaining time before collision (time-to-contact) without requiring any explicit measurement of the relative distance of the animal from the object or the speed of the animal ( Lee, 1976 ; Gibson, 1986 ). From a pure viewpoint of the Gibson’s framework, these perceptual variables can be measured directly by an animal’s visual system (including human's) to estimate the time-to-contact ( Gibson, 1986 ; Serres and Ruffier, 2017 ; Dauxère et al., 2021 ). The relative rate of expansion r or the optical variable τ encodes the ratio of approach velocity V and distance to the landing surface y as r = V / y or τ = y / V ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…Straw et al [15] demonstrated that flies do not use ventral optic flow in their altitude control. Our findings could be expanded or be useful in other insect species to test whether they are sensitive to ventral optic flow, or if other optical information controls their altitude [16]. Our set-up could also be re-scaled to study the effect of optic flow on altitude control in birds [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It provides information about the environment's structure and about the displacement of the agent in relation to these structures [1,2]. Gibson's framework has already proven its suitability in addressing issues related to the control of human displacement [5][6][7][8][9], as well as that of some birds [10][11][12], most flying insects [13][14][15][16][17][18][19][20][21][22][23], and robots [15,17].…”
Section: Introductionmentioning
confidence: 99%